Neurofilament light chain plasma levels in major depressive disorder: a brief research report - Fernández-Pereira, Carlos; Fernández-Ceballos, María de los Ángeles; Olivares, José Manuel; Prieto-González, José M.; Agís-Balboa, Roberto Carlos (Frontiers in Psychiatry, 2024)
IntroductionPeripheral neurofilament light chain (NfL) reflect neuronal and axonal damage. Most studies have been focused on NfL cerebrospinal fluid measures since peripheral levels were difficult to detect. However, with recent advent of single molecule array (SIMOA) technology, NfL is now detectable peripherally at small concentrations (pg/ml). In neurodegenerative disorders, NfL peripheral levels have been found significantly elevated compared against psychiatric disorders. However, there is still controversy of whether NfL peripheral levels might be altered in psychiatric disorders like major depressive disorder (MDD) when compared against a normal population.MethodsWe have measured NfL plasma levels by using single molecule array (SIMOA) technology in a Spanish small cohort of MDD patients (n = 15) and a HC group (n = 15). We have used subjective scales to estimate depression severity (HDRS), anhedonia (SAAS), the general cognitive state (MMSE) and episodic memory (FCSRT) in MDD patients.ResultsWe have not detected a significant alteration in NfL plasma levels in MDD patients when compared against the HC subjects (U = 97, p-value = 0.532). Moreover, we have not detected any significant correlation between NfL plasma levels with any subjective scales. The only parameter that significantly and positively correlated with NfL plasma levels was age in both MDD and HC.DiscussionSignificant alteration in NfL plasma levels in MDD patients might reflect neurobiological changes behind the predisposition to develop future neurodegenerative disorders such as Alzheimer’s or Parkinson’s diseases for which depression represents a risk factor. However, whether there is an increase in NfL due to MDD regardless of the ageing process is still a matter of debate.